2000
DOI: 10.1046/j.1365-277x.2000.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating food and nutrient intake from food frequency questionnaire data by reference to a standard weighed diet survey

Abstract: INTRODUCTION: The food frequency questionnaire is widely regarded as more appropriate for ranking and grouping individuals according to levels of nutrient intake than for estimating absolute nutrient amounts. AIMS: To develop a method for estimation of amount of nutrient intake from food frequency questionnaires by reference to an independent weighed dietary survey. METHOD: Six stages of the method are described and illustrated in the estimation of total dietary fat from the 1984-85 Health and Lifestyle Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Previous studies on EI in these patients have been conducted using self‐reported food diary or food frequency questionnaires (Kalantar‐Zadeh et al ., ; Fassett et al ., ). The weighed food diary method, used in the present study, can be used only in compliant patients because it is complex and difficult to apply; however it is considered to be a gold standard measure (Tefft & Boniface, ; Tokudome et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies on EI in these patients have been conducted using self‐reported food diary or food frequency questionnaires (Kalantar‐Zadeh et al ., ; Fassett et al ., ). The weighed food diary method, used in the present study, can be used only in compliant patients because it is complex and difficult to apply; however it is considered to be a gold standard measure (Tefft & Boniface, ; Tokudome et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Generally, EI per day is estimated through various methods, including 24‐h recall, food frequency questionnaires and the self‐report food intake for ≥1 days, as suggested also by Kidney‐Dialysis Outcome Quality Initiative (K/DOQI) guidelines (National Kidney Foundation K/DOQI, 2000). Nevertheless, all these methods are less reliable (Bingham et al ., ; Schoeller, ) than a weighed food diary, which is considered to be the gold standard measure (Tefft & Boniface, ; Tokudome et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The study has limited generalizability due to the predominantly Euro-American, middle-class sample. Diet was assessed with a food frequency questionnaire, which has recognized limitations (Tefft and Boniface, 2000;Thompson and Subar, 2008).…”
Section: Study Limitations and Strengthsmentioning
confidence: 99%
“…Distributions of food frequency categories reported by the respondents for each food were matched to the corresponding distributions from the weighed intake data provided by the 1986 -87 Dietary and Nutritional Survey of British Adults (DNSBA; Gregory et al, 1990; Office of Population Censuses and Surveys, Social Survey Division 1991). The resultant estimated food weights corresponding to each frequency category, after reference to food composition data, enabled estimates to be made of individual saturated, polyunsaturated and total fat intakes (Tefft & Boniface, 2000). The balance between saturated and polyunsaturated fats intake was represented by (2(saturated fat) 7 (polyunsaturated fat)) Dietary fats and 16 y CHD mortality DR Boniface and ME Tefft as suggested by Keys in his formula relating changes in these fats to changes in serum cholesterol (Keys et al, 1965).…”
Section: The Measuresmentioning
confidence: 99%